Orostylis gen. nov., a new genus of Dalytyphloplanida with seven new species (Platyhelminthes: Rhabdocoela) - Gobert, Stefan; Armonies, Werner; Diez, Yander L.; Jouk, Philippe; Monnens, Marlies; Revis, Nathalie; Reygel, Patrick; Smith , Julian Iii; Steenkiste, Niels Van; Artois, Tom (Zootaxa, 2022)
We describe a new genus of dalytyphloplanid rhabdocoels, with seven new species. Orostylis gen. nov. has a unique combination of characters including the presence of a sclerotised stylet, an anteriorly positioned male copulatory organ with the male genital pore in the buccal cavity, and the absence of an oviduct. The ovary empties directly into the intestinal lumen. Orostylis dohae sp. nov., Orostylis asinaraensis sp. nov., Orostylis caecus sp. nov., Orostylis distortus sp. nov., Orostylis donanae sp. nov., Orostylis gallicus sp. nov., and Orostylis timucuorum sp. nov. are distinguished from each other by the structure of the sclerotised parts of the male copulatory organ. Molecular and morphological evidence place the new genus in Neodalyellida Willems et al. 2006, and similarities with other taxa are discussed.